Sistem Informasi Manajemen Pada CV Anugerah Sejati Prima Menggunakan Metode Single Moving Average - Maulana, Reza; Masyhur, Zulkarnaim; ., Muhammad Ashabul Kahfi (Jurnal INSYPRO (Information System and Processing), 2023)
CV Anugerah Sejati Prima is a trading company that sells various kinds of civil engineering laboratory equipment. In carrying out the inventory management process, periodic checks are still carried out because there is no record of incoming goods so the actual information on the number of stocks in the warehouse is less accurate. The purpose of this research is to create an information system that can be used by CV Anugerah Sejati Prima in assisting the process of recording and managing the inventory of goods. The single-moving average method is used in predicting the number of items to be restocked in the warehouse for the next period's sales. Extreme Programming is used in making this system and black-box as a system testing method. To find out the level of user satisfaction with the system created, the SUS test is carried out where this system is at number 81 which means it has an adjective rating of "Excellent".